Perilaku Bertanggung Jawab Lingkungan: Kesadaran Lingkungan Siswa pada Pendidikan Biologi - Rita Istiana; Eka Suhardi; Novia El Savada Misdaligo; Ilmi Zajuli Ichsan; Diana Vivanti Sigit; Nur Fadli Hazhar Fachrial; Trio Ageng Prayitno; Wiwin Pramita Arif; Ade Imas Rismayati (Department of Biology Education, Faculty of Education and teacher Training, Maritime University of Raja Ali Haji, 2020)
This study aims to obtain information about the relationship between environmental awareness and responsible environmental behavior of students and other factors that influence the environmentally responsible behavior of students. Retrieval of quantitative data using a questionnaire with a rating scale for variables X and Y. Analysis of quantitative data with a prerequisite test in the form of a normality test using the kolmogorov-smirnov test and a homogeneity test using a levene statistic. Testing the data hypothesis using the correlation test with the product moment pearson formula with SPSS 26. Qualitative research data with interviews. Qualitative data analysis by reducing data, presenting data and drawing conclusions. The results showed that there was a positive relationship between environmental awareness and environmentally responsible behavior with the regression equation Å¶ = 99.939 + 0.161x with a correlation coefficient of r = 0.195 and r2 of 3.80%. The price of r2 means that 3.80% of responsible environmental behavior is influenced by environmental awareness, while 96,20% are influenced by other factors. Based on the results of the interview, the factors that can influence environmentally responsible behavior are family, habits, environment (friendship and school environment) and information. Biology education is important to be applied so that students care about the environment.